Metode Pembelajaran Mind Mapping untuk Meningkatkan Kemampuan Komunikasi Matematik Siswa Dalam Pemecahan Masalah Matematika - Faelasofi, Rahma; Arnidha, Yunni; Istiani, Ana (JURNAL E-DUMATH, 2015)
AbstractÂ The objectives of this research was to solve how to increase the mathematical communication skills of students in mathematical problem solving especially on the subject of Statistic. This study aims to determine whether the studentsâ mathematical communication skills of students in mathematical problem solving of the student SMP Muhammadiyah 1 Gadingrejo in the academic year of 2014-2015 using learning method mind mapping on the subject of Statistics can be higher than the studentsâ mathematical communication skills of students in mathematical problem solving without using learning method mind mapping. This research is a quantitative approach, with a quasi-experimental research methods. The population was all of the students in first grade of the SMP Muhammadiyah 1 Gadingrejo in the academic year of 2014-2015. The samples of the research were taken by using the cluster random sampling technique. Based on hypothesis test, it can be included that there are increase the mathematical communication skills of students in mathematical problem solving after using learning method mind mapping on the subject of Statistics of the student in first grade of the SMP Muhammadiyah 1 Gadingrejo in the academic year of 2014-2015. Keywords: learning method mind mapping, mathematical communication skills,mathematical problem solving